PENGELOLAAN WAKAF PRODUKTIF UNTUK KESEHATAN (Studi Kasus Bandha Wakaf Masjid Agung Semarang) - Nurodin Usman (MUADDIB Jurnal Kependidikan dan Keislaman, 2014)
This study describes the management of waqf in the field of health care. The object of waqf in this study is bandha waqf Masjid Agung Semarang which has a land area more than one hundred and thirthy hectares endowsments. Waqf in the field of health care has carried out the moslems from early history of Islam to the present. It also spreads all ove the moslem word, such as in Hijaz, Syam, Egypt, Sudan, and Indonesia. Management of bandha waqf in the field care can be devided into two polyclinics, namely Clinic Masjid Agung Semarang and Clinic Masjid Agung Jawa Tengah. In the futures, it will be developed in the form of a Islamic General Hospital and expected to provide broader health services.